Фискалната децентрализација и макроекономските перформанси во земјите од југоисточна Европа - Макрешанска, Сузана (Економски факултет, УКИМ, Скопје, 2015)
Fiscal decentralization has been a highly ranked public policy goal for many countries over the past two to three decades. In particular, for developing countries in Southeastern Europe, even though the recent decentralization process does not represent the policy goal per se, it reflects the desire for more effective and participatory government and greater voice of local constituents in fiscal policy and the allocation of budgetary resources. Nevertheless, regardless of its motivation and purpose, in some cases the decentralization process has strong positive or negative macroeconomic implications. This PhD dissertation consists of a theoretical and an empirical framework for analyzing the fiscal decentralization process focused on Southeastern European countries. As part of the theoretical framework, the first two chapters deal with concepts and measurement of the intergovernmental fiscal relations, with a particular focus on the role and importance of local governments. The next four chapters are part of the empirical framework and explore the impact of decentralization on the public sector size and macroeconomic performance over the last two decades. Using a panel data set, this dissertation shows that fiscal decentralization contributes to smaller and more efficient public sectors in Southeastern European countries. Furthermore, the empirical results indicate that, unlike for developed European countries, for Southeastern European countries decentralization and economic growth are not directly proportional to each other. This means that in certain cases an increased amount of fiscal decentralization has a negative impact on economic growth. The negative impact on growth is, however, partially neutralized by the positive impact on macroeconomic stability through improving fiscal performance and price stability. Finally, this dissertation shows that fiscal decentralization increases income inequality, which is also further pronounced when local governments are financed from their own fiscal capacities rather than by fiscal transfers from the central government.
Fiscal decentralization and macroeconomic performance in Southeastern European countries
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Горан Петревски.
Keywords: fiscal decentralization, decentralization indicators, size of public sector, macroeconomic implications, economic growth, fiscal performance, inflation, income inequality, Southeastearn European countries